2020
DOI: 10.1088/1755-1315/441/1/012136
|View full text |Cite
|
Sign up to set email alerts
|

Utility of almond leaf (Terminalia cattapa) for improving growth and color quality of neon tetra fish (Paracheirodon innesi)

Abstract: Ornamental fish farming is easy to stress, which results in fading colors and patterns of the body. The effort to maintain the color and pattern of the fish’s body are using Almond leaf. This study aims to obtain the optimum concentration of Almond leaf in the maintenance of neon tetra fish, which is expected to improve the color quality and growth of fish. Neon tetra fish seeds measuring 1 - 2 cm were maintained in an aquarium sizing 25 cm x 40 cm x 28 cm with a stocking density of 4 tails liter−1. The comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…Another study reported enhancements in growth parameters across several species following rearing in Indian almond leaf extract at appropriate concentrations (Ikhwanuddin et al, 2014;Nurhidayat et al, 2016;Ramos et al, 2020). Nevertheless, excessive concentrations of these extracts have been proven detrimental to aquatic fauna, such as the neon tetra fish, Paracheirodon innesi (Ardi et al, 2020), the black tiger shrimp, Penaeus monodon (Ikhwanuddin et al, 2014), the Siamese fighting fish, Betta sp. (Nugroho et al, 2016(Nugroho et al, , 2017Malawa et al, 2022), the cardinal tetra, Paracheirodon axelrodi (Nurhidayat et al, 2016) and the Amazon leaf fish, Monocirrhus polyacanthus (Ramos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported enhancements in growth parameters across several species following rearing in Indian almond leaf extract at appropriate concentrations (Ikhwanuddin et al, 2014;Nurhidayat et al, 2016;Ramos et al, 2020). Nevertheless, excessive concentrations of these extracts have been proven detrimental to aquatic fauna, such as the neon tetra fish, Paracheirodon innesi (Ardi et al, 2020), the black tiger shrimp, Penaeus monodon (Ikhwanuddin et al, 2014), the Siamese fighting fish, Betta sp. (Nugroho et al, 2016(Nugroho et al, , 2017Malawa et al, 2022), the cardinal tetra, Paracheirodon axelrodi (Nurhidayat et al, 2016) and the Amazon leaf fish, Monocirrhus polyacanthus (Ramos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the coloration of ornamental fish can serve as a crucial indicator not only of their aesthetic quality but also of their health status (Yi et al, 2021). Nonetheless, the injury stress that occurred during the caudal fin regeneration and color development processes, as documented in the report by Malawa et al (2023), is a possible factor influencing various physiological processes, including altered shades of body color (Ardi et al, 2020). The current findings identified notable changes, such as significant decreases in some body color parameters (a*, h*, C*) in the injured fish in all herbal treatments, except for CT 2 relative to CT 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final BW of neon tetras was significantly higher than the starting BW only in the T group. Among the few papers on P. innesi which could provide a point of reference [ 29 , 30 , 31 , 62 , 63 , 64 , 65 , 66 , 67 ], it was established that these characids prefer high-protein diets (>50%) [ 30 , 31 ] and that animal protein provides better growth rates than plant protein [ 30 ]. This might be a slight suggestion that of the two tested commercial feeds, the protein content/origin of TetraMin flakes was preferred by neon tetras, at least due to its higher total dietary percentage (47.8%, as opposed to 43.3% in the Omega flakes).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, breeding protocols were already developed years ago, including actual scientific research [ 58 , 59 , 60 , 61 ]. Meanwhile, some relatively basic feeding-oriented studies were conducted on the species [ 29 , 30 , 31 , 62 , 63 , 64 , 65 , 66 , 67 ] and its congener, the cardinal tetra Paracheirodon axelrodi (Schultz, 1956) [ 34 ], but only standard body morphometrics were reported, without providing any insight into the structure and condition of internal organs.…”
Section: Introductionmentioning
confidence: 99%